As Licenciaturas em Química EaD nos IF e a Heutagogia como elemento basilar nos modelos de formação docente - Alves, Dylan Ávila (2024)
This research aims to investigate the educational methodologies present in distance Chemistry Licentiate courses (LQ). It utilizes the theoretical perspectives of adult education in distance courses (Heutagogy) proposed by Stewart Hase and Chris Kenyon. The goal is to contribute to the discussion of the methodologies used in distance Chemistry courses at Federal Institutes (IF) that facilitate the learning process in these courses. The doctoral thesis was structured from chapters in the format of articles. For the conclusion of the thesis, three chapters/articles were developed titled: 1- Tensions in the Landscape of Chemistry Licentiate Programs in Brazil: Distance Education in Public and Private Spheres; 2- Heutagogy as a Methodology for Teacher Training at a Distance: An Overview of Brazilian Research; 3- An Analysis of Distance Chemistry Licentiate Programs in Federal Institutes from the Perspective of Heutagogical Learning Design Elements. Chapter 1 presents results from the survey of distance Chemistry Licentiate programs (LQ) in public and private higher education institutions (IES) in 2021, conducted through the e-MEC portal. A descriptive study with a quantitative-qualitative approach was used. The distance LQ programs represent a total of 20 courses in public institutions and 25 in private ones. The study highlights a trend towards teacher training through distance education, especially in private IES, but it also indicates the need for public institutions to investigate distance education training. Chapter 2 presents a survey of the main publications related to the Heutagogy theme in the Database of Theses and Dissertations (BDTD) from CAPES and in Portuguese journals. The research is configured as the "state of the art," divided into two moments: the first addresses the inventory of publications from 2010 to 2022, and the second identifies the trends in the publications regarding the theme. A total of 14 publications were surveyed, including five in the BDTD and nine in scientific articles. Initially, an analysis category was established as "Teacher Training," but two categories emerged: Distance Education and Heutagogy as a methodology. The study shows that there is no clear direction in research towards teacher training courses, but it presents Heutagogy as a potential theoretical reference in distance Licentiate courses. Chapter 3 analyzes the curricular proposals (PPC) of distance LQ courses in IF, based on the six learning elements proposed by Blaschke and Hase (2016). It was possible to reveal that the LQ programs present some learning elements in the documents, which can be evidenced in disciplines, evaluation criteria, supervised internships, curricular components, tutorial activities, among others.